2018
DOI: 10.1021/acssuschemeng.8b00984
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Supported Monometallic Catalysts in the Liquid-Phase Hydrogenation of Furfural: Batch Versus Continuous Flow

Abstract: This work compares the catalytic performance of well-defined monometallic catalysts supported on commercial microporous/mesoporous carbon (Cu/AC, Pd/AC, Pt/ AC, and Ni/AC) for the liquid-phase hydrogenation of furfural, both in batch and in continuous flow. Whereas Ni/ AC performed better in batch (in terms of selectivity to 2methylfuran), better results were obtained with Pt/AC in continuous flow. Reutilization of the Ni/AC catalyst recovered by simple filtration after batch experiments changed the selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 48 publications
0
44
0
Order By: Relevance
“…For comparison, our research group recently found that Ni/C was selective to MF at 200 • C with H 2 or 260 • C without H 2 in batch conditions; however, in continuous flow regime at 150 • C under 50 bar H 2 , the hydrogenation selectivity was quite poor due to side-reaction between furfural and isopropanol. When altering the solvent with non-protic cyclopentyl methyl ether (CPME), two major products, namely FA and THFA, were obtained [141]. These results gave a clear hint that selective hydrogenation could be achieved by changing the reaction regime and conditions.…”
Section: Co Ni Based Catalystmentioning
confidence: 94%
“…For comparison, our research group recently found that Ni/C was selective to MF at 200 • C with H 2 or 260 • C without H 2 in batch conditions; however, in continuous flow regime at 150 • C under 50 bar H 2 , the hydrogenation selectivity was quite poor due to side-reaction between furfural and isopropanol. When altering the solvent with non-protic cyclopentyl methyl ether (CPME), two major products, namely FA and THFA, were obtained [141]. These results gave a clear hint that selective hydrogenation could be achieved by changing the reaction regime and conditions.…”
Section: Co Ni Based Catalystmentioning
confidence: 94%
“…[40] We have designed and evaluated the reduction of acetophenone to 1-Phenyl ethanol as model substrate using sodium borohydride and water as a solvent. [41] - [42] 2. Experimental…”
Section: Introductionmentioning
confidence: 99%
“…However, after the fourth cycle, the conversion of furfural dropped from 100% to 69% and the selectivity to FOL also decreased (88%). This could be due to the poisoning of cobalt in the solution, as this is already mentioned in the literature, or to the leaching of cobalt, [24,26] leading to the formation of by-products such as THFA and other unidentified by-products. To confirm these hypotheses, TGA analysis of the spent catalyst were performed and compared to the TGA analysis of the fresh catalyst (Figure 4).…”
Section: Hydrogenation Of Furfural In Batch Reactormentioning
confidence: 87%
“…Several drawbacks are present using this system: deactivation due to the sintering of active species; poisoning of the catalyst surface by coke formation; low selectivity of FOL; and high temperature and pressure. Up to now, several studies of selective hydrogenation of furfural to FOL have been performed in the liquid phase in batch reactors using different solvents, but very little attention has been paid to the process in a flow system [22][23][24][25][26]. To this aim, hydrogenation of furfural to FOL was studied in the presence of Co/SiO 2 catalyst in batch and in continuous flow reactors.…”
Section: Methodsmentioning
confidence: 99%